Shape Programming and Dielectric Properties of ZnO Nanoparticle/PVA Shape Memory Polymer Based Thermal Actuators - Dere, Aysegul; Demirelli, Kadir; Mansour, Shehab A.; Yakuphanoğlu, Fahrettin (Wiley, 2025)
The zinc oxide nanoparticles (ZnO NPs) were prepared by the hydrothermal process. The ZnO NPs were doped into the PVA matrix, and nanocomposite films were produced by the solution casting method. The thermal degradation temperatures of PVA/ZnO nanocomposites are slightly lower than those of pure PVA. While the degradation of three nanocomposites up to about 375 degrees C occurs at lower temperatures compared to pure PVA, it occurs at higher temperatures compared to PVA above about 400 C due to the drastic change of the PVA chain structure. The incorporation of ZnO NPs into the PVA matrix causes a remarkable change in the degradation mechanism. The structural characterization studies of PVA/ZnO nanocomposite films revealed significant changes in their dielectric and thermal properties. This change indicates that PVA/ZnO nanocomposite films exhibited a thermal actuator behavior. The increase in the dielectric constant with increasing ZnO content at room temperature facilitates the orientation of electrons and increases the polarization associated with the movement of electrons. The dielectric parameters such as dielectric constant, dielectric loss, and impedance of the PVA/ZnO nanocomposite films are controlled by ZnO nanoparticles. The improvements in dielectric properties are indicative of a good interaction between ZnO NPs and the PVA matrix. Thermal and dielectric results explain the behavior of PVA/ZnO nanocomposites as thermal actuators. The obtained results suggest that the shape programming of ZnO nanoparticles/PVA shape memory polymer-based thermal actuators is explained by thermal and dielectric properties.
Keywords: dielectric properties; PVA; shape memory; ZnO nanoparticle